2012
DOI: 10.1021/cm202976e
|View full text |Cite
|
Sign up to set email alerts
|

Selective Sorption of Olefins by Halogen-Substituted Macrocation-Polyoxometalate Porous Ionic Crystals

Abstract: Ionic crystals [Cr3O(OOCCH2 X)6(H2O)3]4[α-SiW12O40]·14H2O (X = Cl [Ia], Br [IIa]) are synthesized by complexation of halogen-substituted macrocations with a silicododecatungstate. Compounds Ia and IIa possess analogous one-dimensional winding channels, and the channel walls are composed of oxygen atoms of silicododecatungstates and −CH2 X groups of macrocations. Water of crystallization in Ia (IIa) is desorbed by the treatment in vacuo or under a dry N2 or He flow at 298–303 K, and the corresponding guest free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…The unsaturated hydrocarbons acetylene, ethylene, and propylene display the side- ) was reported by Mizuno and co-workers. 105 They are built up from halogen-substituted macrocations and polyoxometalates (POMs). These two compounds possess analogous one-dimensional winding channels, and the channel 30 walls are composed of oxygen atoms of silicododecatungstates and CH 2 X groups of macrocations.…”
Section: Equilibrium Based Mechanismmentioning
confidence: 99%
“…The unsaturated hydrocarbons acetylene, ethylene, and propylene display the side- ) was reported by Mizuno and co-workers. 105 They are built up from halogen-substituted macrocations and polyoxometalates (POMs). These two compounds possess analogous one-dimensional winding channels, and the channel 30 walls are composed of oxygen atoms of silicododecatungstates and CH 2 X groups of macrocations.…”
Section: Equilibrium Based Mechanismmentioning
confidence: 99%
“…Ionic crystals, which are important families of crystalline materials, have been attracting considerable interest because of their unique chemical and physical properties, which depend on their crystalline structures and constituent ions [1][2][3][4][5][6][7][8][9]. Normally, cations and anions are densely packed in the crystal lattice, with the coordination numbers determined by the relative sizes and charges of the constituent ions since the Coulombic forces are strong and directionless.…”
Section: Introductionmentioning
confidence: 99%
“…Mizuno et al reported that olefins such as ethylene and propylene are preferentially adsorbed in the ionic crystals [Cr 3 O(OOCCH 2 X ) 6 (H 2 O) 3 ] 4 [α‐SiW 12 O 40 ]·14H 2 O ( X = Cl or Br) . Different from MOFs where metal moieties are interconnected via coordination bonds, these porous ionic crystals are composed with 0‐D coordination complexes and polyoxometalate anions ( Figure a,b).…”
Section: Other Porous Materials For Adsorptive Light Olefin/paraffin mentioning
confidence: 99%
“…d) Local structure of the 1D channel. e) C 2 H 4 (circle) and C 2 H 6 (square) sorption isotherms of [Cr 3 O(OOCCH 2 Cl) 6 (H 2 O) 3 ] 4 [α‐SiW 12 O 40 ] and [Cr 3 O(OOCCH 2 Br) 6 (H 2 O) 3 ] 4 [α‐SiW 12 O 40 ] at 298 K. Modified and reproduced with permission . Copyright 2012, American Chemical Society.…”
Section: Other Porous Materials For Adsorptive Light Olefin/paraffin mentioning
confidence: 99%